Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The followings are from Kai Lai Chung's A Course in Probability Theory, on page 207

$X_{n,j}, j=1,\dots, k_n, n=1,\dots,$ are random variables, where $k_n \to \infty$ as $n\to \infty$.

For every $\epsilon > 0$:

(a) for each $j$, $\lim_n P(|X_{nj}|>\epsilon) = 0$;

(b) $\lim_n \max_j P(|X_{nj}| > \epsilon) = 0$; (holospoudic)

(c) $\lim_n P(\max_j |X_{nj}| > \epsilon) = 0$;

(d) $\lim_n \sum_j P(|X_{nj}| > \epsilon) = 0$;

It is clear that (d) => (c) => (b) => (a).

I can understand (d) => (c), because $$\sum_j P(|X_{nj}| > \epsilon) \geq P(\max_j |X_{nj}| > \epsilon).$$

I can understand (b) => (a), because $$\max_j P(|X_{nj}| > \epsilon) \geq P(|X_{nj}|>\epsilon).$$


  1. I wonder why (c) => (b)? Neither do I understand why $$P(\max_j |X_{nj}| > \epsilon) \geq \max_j P(|X_{nj}| > \epsilon),$$ if it is true.
  2. Also why when $X_{nj}, j=1,\dots,k_n$ are independent for each $n$, (d) $\equiv$ (c)? This is in the exercise 1 on page 214.

Thanks and regards!

share|cite|improve this question
up vote 2 down vote accepted

Fix $\varepsilon$, and consider some random variables $(Y_k)_k$ and $Y=\sup\limits_kY_k$. For every $i$, $Y\geqslant Y_i$ hence $[Y_i\gt\varepsilon]\subseteq[Y\gt\varepsilon]$. This implies that $\mathrm P(Y_i\gt\varepsilon)\leqslant\mathrm P(Y\gt\varepsilon)$. This inequality holds for every $i$ and the RHS does not depend on $i$ hence $\sup\limits_i\mathrm P(Y_i\gt\varepsilon)\leqslant\mathrm P(Y\gt\varepsilon)=\mathrm P(\sup\limits_iY_i\gt\varepsilon)$.

Edit: When, furthermore, the random variables $(Y_k)_k$ are assumed independent, the estimation of the distribution of $Y$ proceeds as usual. First, for every $\varepsilon$, $[Y\leqslant\varepsilon]=\bigcap\limits_k[Y_k\leqslant\varepsilon]$ hence $$ \mathrm P(Y\gt\varepsilon)=1-\prod\limits_k(1-\mathrm P(Y_k\gt\varepsilon)). $$ Now, $1-x\leqslant\mathrm e^{-x}$ for every $x$ hence $$ \mathrm P(Y\gt\varepsilon)\geqslant1-\exp\left(-\sum\limits_k\mathrm P(Y_k\gt\varepsilon)\right), $$ which shows that (c) implies (d). On the other hand, (d) implies (c) because $[Y\gt\varepsilon]=\bigcup\limits_k[Y_k\gt\varepsilon]$ and the probability of the union is at most the sum of the probabilities.

share|cite|improve this answer
Thanks, Didier! I understand the first question now. I wonder why (d) and (c) are equivalent when $X_{nj},j=1,\dots,k_n$ are independent for each $n \in \mathbb{N}$? – Tim Jul 1 '12 at 14:49
See Edit. $ $ $ $ – Did Jul 1 '12 at 17:38
Thanks! (d) => (c), can it be because $$\sum_k P(|Y_k| > \epsilon) \geq P(Y > \epsilon)$$? – Tim Jul 1 '12 at 17:59
Yes. $ $ $ $ $ $ – Did Jul 1 '12 at 18:29
$[Y⩽ε]=⋂_k[Y_k⩽ε]$, I think $[Y⩽ε] \supseteq ⋂_k[Y_k⩽ε]$ is more accurate, given $Y = \sup_k Y_k$, isn't it? $Y_k$ being independent doesn't make the inequality equality. – Tim Jul 2 '12 at 4:10

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.